RETRACTED: Irrigation and production of seeds of various sesame varieties in the conditions of Karakalpakstan - Mambetnazarov B.S.; Bekbanov B.A.; Mambetnazarov A.B.; Aybergenov B.; Quwanishbaeva Sh.D.; Mambetnazarov B.B. (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001